Quiescence modulates age-related changes in the functional capacity of highly proliferative canine lung mesenchymal stromal cell populations - Nakesha Agyapong; Leslie Dominguez-Ortega; Brian Macdonough; Patrick Mulluso; Sagar Patel; Briti Prajapati; Brian Saville; Andrew Shapiro; Ethan Trim; Kara Battaglia; Jocelyn Herrera; Gianna Garifo-MacPartland; et al. (PLoS ONE, 2025)
The functional capacity of highly proliferative cell populations changes with age. Here, we report that the proliferative capacity of canine lung mesenchymal stromal cells (LMSCs) declines with increasing age of the donor. However, other functional changes such as reduced autophagy, reduced migration/wound healing, increased production of reactive oxygen species, and increased senescence are not significantly altered with increasing age. Furthermore, transcriptomic profiling suggests minimal age-related changes. These data suggest that the reduced proliferative capacity of lung LMSCs isolated from aging donors may be associated with reversible cell cycle arrest (quiescence), rather than irreversible cell cycle arrest (senescence). Similar findings have been reported in other systems, including neural and muscle stem cells that are associated with low turnover-rate tissues.